FAKTOR–FAKTOR YANG MEMPENGARUHI KEPATUHAN MEMBAYAR PAJAK WAJIB PAJAK ORANG PRIBADI YANG BERWIRAUSAHA DENGAN LINGKUNGAN SEBAGAI VARIABEL MODERASI (Studi Empiris di KPP Pratama Kudus) - Tantra Ikhlas Nalendro; Jaka Isgiyarta (Diponegoro Journal of Accounting, 2014)
The Government until this time relies on tax revenue as a major source of development funds so that taxpayers are expected to have a high tax compliance. However, the reality reveals that most of taxpayers have no compliance. It is indicated by paying taxes late and try to do the tax evasion. This study aims to test empirically and analyze the effect of willingness to pay taxes, knowledge andunderstanding of taxpayers, perception of taxpayers financial condition, environtmen as moderating towards tax compliance. The proposed hypothesis are willingness to pay taxes, knowledge andunderstanding of taxpayers, perception of taxpayers financial condition have a positive influence towards tax compliance and moderated by environtment.The research was conducted by survey method to individual tax payers in the Kudus city who perform as an enterpreneur, which is obtained by incidental sampling. Data collection method used questionnaires at 2014 toward 100 respondent, and further data were analyzed using multiple regression analysis.The results of this research indicated that willingness to pay taxe and perception of taxpayers financial conditionhad a significant effect toward tax compliance. But knowledge and understanding of taxation law do not had a significant effect toward tax compliance. And the environtment positively moderating effect of willingness to pay taxes, knowledge andunderstanding of taxpayers, perception of taxpayers financial condition toward tax compliance.